2015
DOI: 10.1111/add.12917
|View full text |Cite
|
Sign up to set email alerts
|

Is the use of electronic cigarettes while smoking associated with smoking cessation attempts, cessation and reduced cigarette consumption? A survey with a 1‐year follow‐up

Abstract: AimsTo use a unique longitudinal data set to assess the association between e‐cigarette use while smoking with smoking cessation attempts, cessation and substantial reduction, taking into account frequency of use and key potential confounders.DesignWeb‐based survey, baseline November/December 2012, 1‐year follow‐up in December 2013.SettingGreat Britain.ParticipantsNational general population sample of 4064 adult smokers, with 1759 (43%) followed‐up.MeasurementsMain outcome measures were cessation attempt, cess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
208
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(236 citation statements)
references
References 35 publications
(47 reference statements)
22
208
3
3
Order By: Relevance
“…This finding is plausible because even heavier adolescent smokers tend to be more nicotine-dependent [25] and would use e-cigarettes more heavily. It has been suggested that intensive or daily use of e-cigarettes, especially the tank type, may increase the chances of quitting smoking among adults [14,15]; however, no cessation aid, including e-cigarettes, has proved to be effective among adolescents [26]. Moreover, considering the potential adverse effect of nicotine on adolescent brain development [27], heavier e-cigarette use would likely cause more potential harm than benefit among adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is plausible because even heavier adolescent smokers tend to be more nicotine-dependent [25] and would use e-cigarettes more heavily. It has been suggested that intensive or daily use of e-cigarettes, especially the tank type, may increase the chances of quitting smoking among adults [14,15]; however, no cessation aid, including e-cigarettes, has proved to be effective among adolescents [26]. Moreover, considering the potential adverse effect of nicotine on adolescent brain development [27], heavier e-cigarette use would likely cause more potential harm than benefit among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to distinguish established users from non-established users because there is a difference in the reason for e-cigarette initiation in addition to the extent of its use [13]. According to previous studies considering current cigarette smokers, the successful smoking cessation rate was higher among daily or intensive e-cigarette users compared with nondaily or intermittent users [14][15][16]. 2 of 8 The general concept of current e-cigarette use is broadly defined to differentiate experimenters from regular users.…”
Section: Introductionmentioning
confidence: 99%
“…The same study [9] found daily ENDS users reduced daily smoking frequency significantly, but four cohort studies [11][12][13] have now reported that even 50% reductions do not confer either any or significant risk reductions compared to smoking cessation. Dual use, far more common in daily vapers than exclusive ENDS use, is not harm-reducing; so, again, high-minded ethical exhortations about reducing harm remain questionable.…”
mentioning
confidence: 95%
“…All have been criticized for including non-daily users in their analyses, but the most recent study which separated daily from non-daily users also found no statistically significantly differences between daily, less than daily and non-vaping smokers for smoking cessation [9]. A sub-analysis found that daily 'tank' vapers were more likely to quit, although nearly three quarters of these were still dual using at 12 months and the proportions of smokers involved were small [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation